Birth anthropometry predicts neonatal and infant mortality in rural Bangladesh: a focus on circumferential measurements. Issue 5 (11th January 2022) - Kang, Yunhee; Wu, Lee Shu Fune; Shaikh, Saijuddin; Ali, Hasmot; Shamim, Abu Ahmed; Christian, Parul; Labrique, Alain; West, Keith P
ABSTRACT: Background: Low birth weight predicts risk of infant death. However, several birth measurements may be equally predictive, for which cutoffs and associated risks are less explored. Objectives: We assessed and optimized population cutoffs of birth length, weight, and midupper arm circumference (MUAC), head circumference (HC), and chest circumference (CC) for predicting neonatal (≤28 d) and infant (≤365 d) mortality in northwest Bangladesh. Methods: Among 28, 026 singletons born in an antenatal micronutrient supplement trial, 21, 174 received anthropometry ≤72 h after birth, among whom 583 died in infancy. Optimization for predicting mortality for each measurement was guided by the Youden Index (sensitivity + specificity – 1). Relative risk ratios (RRRs) and positive predictive values (PPVs) were calculated across cutoff ranges for individual and any pair of measurements. Results: Optimal cutoffs, harmonized to 100-g or 0.5-cm readings, for neonatal and infant mortality were 44.5 cm for length, 2200 g for weight, 9.0 cm for MUAC, 31.0 cm for HC, and 28.5 cm for CC, below which all predicted mortality. However, a CC <28.5 cm, alone and combined with HC <31.0 cm, yielded the highest RRR [9.68 (95% CI: 7.84, 11.94) and 15.74 (95% CI: 12.54, 19.75), respectively] and PPV (11.3% and 10.7%) for neonatal mortality and highest RRR [6.02 (95% CI: 5.15, 7.02) and 9.19 (95% CI: 7.72, 10.95)] and PPV (16.3% and 14.5%) for infant mortality. Pairs of measurements revealed a higher RRR for neonatal and infant mortality than individual measurements of any one pair, although the ranges of PPV remained comparable. Conclusions: In Bangladesh, multiple birth measurements alone or in combination, particularly chest circumference, predict neonatal and infant mortality.